Status dan tahap penggunaan jentera dan mesin di kalangan kontraktor G7 di Malaysia - Azman, Mohamed Nor Azhari; Mohd Zaihidee, Fardila; Mohd Nawi, Mohd Nasrun; Mohamad Kamar, Kamarul Anuar; Abd Hamid, Zuhairi; Mustapha, Ramlee; Khuan, Wai Bing; Tee, Tze Kiong (Penerbit UTM Press, 2014)
The wide use of machine and machinery in the construction industry can reduce the dependency on foreign workers.The Construction Industry Development Board is formulating a strategic plan to promote the use of machine and machinery in the construction industry. Therefore, this study aims to study the level and status of the usage machine and machinery among the G7 contractors at construction sites. The instrument used in the study consist of questionnaire and interviews. Based on the literature findings, there are 9 types of machine and 9 types machinery used in the construction industry.The percentage use of machine and machinery as well as the level of mechanisation for each phase of construction is at level 1, where the machine and machinery is still driven by the operator and do not involved high technology. The main recommendation in this study is to provide training on the latest information on machine and machinery and CPD (Continue Professional Development) training to promote the use of machine and machinery.In addition, the offering better incentives such as tax breaks and loan facilities should be awarded and provided by the government to activate the economic growth.